2019
DOI: 10.1021/acs.jafc.9b00070
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically Induced Controlled Glycation of Lysozyme and Its Effect on Enzymatic Activity and Conformational Changes

Abstract: Protein glycation through heating of a mixture of protein and reducing sugars is one of the most commonly used methods of protein modification; however, in most cases, this approach can lead to uncontrolled glycation. The hypothesis that mechanical energy supplied through ball milling can induce glycation of proteins was tested using a well-characterized enzyme lysozyme. The Q-TOF/MS analysis of the milled samples has indicated that the milling of sugar−protein mixtures in stainless steel jars for 30 min and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Lysozyme can be protected by polyols and sugars versus heat, because they affected hydrophobic interactions ( 44 ). Xing and Yaylayan stated that the presence of sugars could even maintain the enzymatic activity of lysozyme after milling ( 48 ). The most important factors that affect the catalytic rate of lysozyme are shown in Figure 2 .…”
Section: Antimicrobial Activity Of Lysozymementioning
confidence: 99%
“…Lysozyme can be protected by polyols and sugars versus heat, because they affected hydrophobic interactions ( 44 ). Xing and Yaylayan stated that the presence of sugars could even maintain the enzymatic activity of lysozyme after milling ( 48 ). The most important factors that affect the catalytic rate of lysozyme are shown in Figure 2 .…”
Section: Antimicrobial Activity Of Lysozymementioning
confidence: 99%
“…Lysozyme is a protein consisting of ~40% of the α-helical structure and has six lysine residues and eleven arginine residues as potential glycation sites [84,85]. Studies previously showed that glycation alters conformation of lysozyme secondary and tertiary structures, and the loss of α-helix results in reduction in its bactericidal and enzymatic activity, thereby increasing susceptibility to bacterial infections in diabetes [86][87][88].…”
Section: Plos Onementioning
confidence: 99%
“…The most probable assignments of molecular vibrations at the 12 wavenumber positions are as follows: 1338 cm –1 (the ring vibration of tryptophan), 1404 cm –1 (the symmetric COO – vibrations of aspartate and glutamate side chains), 1454 cm –1 (the amide II′ mode), 1514 cm –1 (the ring vibration of tyrosine), 1545 cm –1 (the amide II mode for β-sheet), 1549 cm –1 (the amide II mode), 1560 cm –1 (the amide II mode for α-helix), , 1583 cm –1 (the asymmetric COO – vibrations of aspartate and glutamate side chains), 1609 cm –1 (the ring vibration of tyrosine and the CN 3 H 5 + side-chain vibration of arginine), 1630 cm –1 (the amide I′ mode), 1651 cm –1 (the amide I mode), and 1686 cm –1 (the amide I mode for β-turn). , Please note that the band assignment to a wavenumber position does not perfectly correspond to the molecular vibration of a small group of a lysozyme molecule because of the overlapping of bands. But when a band overlapping is not too large and the band is situated more separately, one may discuss the sequential order of the physical/chemical “events” of small groups of a lysozyme molecule.…”
Section: Application To the Infrared Spectra Of An H–d Exchange Proce...mentioning
confidence: 99%